Renal transplantation and cytomegalovirus retinitis - (:unkn) unknown (My University, 2000)
0

We report a case of cytomegalovirus retinitis in a 63 year old man who underwent renal transplantation 7 months ago. He was treated with parenteral ganciclovir and effective response occurred after 4 weeks treatment.
Keywords: Genel ve Dahili Tıp